2017
DOI: 10.1038/s41598-017-06293-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contributions by frontal and parietal cortices support working memory

Abstract: Although subregions of frontal and parietal cortex both contribute and coordinate to support working memory (WM) functions, their distinct contributions remain elusive. Here, we demonstrate that perturbations to topographically organized human frontal and parietal cortex during WM maintenance cause distinct but systematic distortions in WM. The nature of these distortions supports theories positing that parietal cortex mainly codes for retrospective sensory information, while frontal cortex codes for prospecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 36 publications
2
38
1
Order By: Relevance
“…These lesion results are supported by a recent transcranial magnetic stimulation study in which disruption of human dlPFC did not affect accuracy of memory-guided saccades (Mackey and Curtis, 2017 ). However, disruption of topographically-organized precentral sulcus and intraparietal sulcus regions impaired SWM accuracy (Mackey and Curtis, 2017 ) in a way that is consistent with analogous studies in macaque frontal eye fields (FEF) and lateral intraparietal area (LIP). Taken together, the data suggest that the dlPFC circuits that subserve SWM in macaque monkeys may not have a direct homolog in human dlPFC but that other frontal and parietal regions that support SWM may be more homologous in the two species.…”
Section: Discussionsupporting
confidence: 69%
“…These lesion results are supported by a recent transcranial magnetic stimulation study in which disruption of human dlPFC did not affect accuracy of memory-guided saccades (Mackey and Curtis, 2017 ). However, disruption of topographically-organized precentral sulcus and intraparietal sulcus regions impaired SWM accuracy (Mackey and Curtis, 2017 ) in a way that is consistent with analogous studies in macaque frontal eye fields (FEF) and lateral intraparietal area (LIP). Taken together, the data suggest that the dlPFC circuits that subserve SWM in macaque monkeys may not have a direct homolog in human dlPFC but that other frontal and parietal regions that support SWM may be more homologous in the two species.…”
Section: Discussionsupporting
confidence: 69%
“…Although electrical stimulation of an FEF neuron elicits an eye movement of a fixed magnitude and direction, SEF stimulation elicits an eye movement to a fixed region of the visual field relative to the position of the head, irrespective of the starting position of the eye ( 47 ). Although much less is known about topographic organization in SEF, a recent human neuroimaging study suggests it also contains an orderly map of continuous space similar to other visual areas ( 48 ).…”
Section: Ehc Neurophysiology and Neuroanatomymentioning
confidence: 99%
“…All three papers used the identical method to localize and define dlPFC, first finding the motor hand area and then moving anteriorly a few centimeters; this method has also been described as an effective way to localize the human FEF ( 70 ). A more recent study using TMS to disrupt activity in human dlPFC found no impairment on memory-guided saccades ( 48 ).…”
Section: Ehc Neurophysiology and Neuroanatomymentioning
confidence: 99%
“…It is important to emphasize, again, that our findings do not reflect a general, unspecific preparation of an effector or action [ 13 , 25 , 26 ], as this was controlled for by our control task. We also ensured through our task design that there is a clear separation between the memory maintenance and the preparation of any specific motor action throughout the delay period, a problem that has been extensively highlighted in other works [ 10 , 11 , 17 ]. This was because in our experiment an action could only be planned and executed after the delay when the test set was shown.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it might be the prospective action plan that is (additionally) maintained in WM in such situation. Experimental support has been provided in support of this conceptual distinction between retrospective and prospective information maintenance: Studies of Curtis and colleagues [ 11 , 17 ] and Lindner and coworkers [ 14 ] report differences in brain activity whenever spatial objects not only had to be remembered but, at the same time, were targets to which saccades [ 11 ] or reaches [ 14 ] should be directed. Yet, in spite of these reported differences, both working memory and action planning tasks recruit an almost identical set of posterior parietal and frontal areas, reflecting strong functional ties between the two aspects of the perception-to-action processing stream [ 2 , 11 , 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%